Distribution of DNA insertion element IS5 in natural isolates of Escherichia coli. - Green, L (1984)
DNA from Escherichia coli strains in a reference collection of 72 recent natural isolates (ECOR strains) and 25 natural isolates from the "pre-antibiotic" period 1930-1940 (Murray strains) were studied to determine the genomic abundance of insertion element IS5 and the size of genomic restriction fragments carrying sequences homologous to IS5. Among the ECOR strains, nearly two-thirds lack DNA sequences that hybridize with IS5, and one-half of the remainder have only one copy. Among strains in which IS5 is present, extensive variation in the size of IS5-bearing restriction fragments occurs, in many cases allowing distinction among strains that are judged to be nearly identical in genotype because of the identical electrophoretic mobility of the enzyme coded by each of 11 chromosomal loci. Among the Murray strains in which IS5 is present, the average number of elements per strain is larger, but not markedly so, than among recent isolates. Comparison between duplicate strains in the Murray collection suggests that the rate of accumulation of IS5 elements in prolonged storage in stab tubes corresponds to an apparent probability of transposition of approximately 0.008 +/- 0.002 per IS5 element per year. Because of the extensive genetic variation among strains, insertion elements such as IS5 would seem to be convenient genetic markers with which to detect recent common ancestry among strains.